PENGARUH EARNING PER SHARE, PRICE TO BOOK VALUE, CASH FLOW OPERATING, STOCK RETURN, DIVIDEND PAYOUT RATIOTERHADAP PENILAIAN EKUITAS PERUSAHAAN - Yanti, Sharen Santoso Rafli, (Jurnal Ekonomi, 2015)
The purposeof this studyis to analyze the effect of Earnings Per Share, Price to Book Value, Cash Flow Operating, Stock Return, Dividend Payout Ratio to theEquity Valuation oncompanies listedinthe Indonesia Stock Exchange. A total sample of 47 manufacturing company was selected through purposive sampling method. The results of this study is the earnings per share, dividend payout ratio, and operating cash flow do not have significant influence on equity valuation. Conversely, the price-to-book value and stock return       have  significant influence on equity valuation. Suggestions for future research is to expand the period of research and use others independent variables that have not been tested in this study for example: sales, interest rates, retained earnings, stock price, and net income.